2019
DOI: 10.5539/sar.v8n4p28
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Nelore Cows of the Bolivian Tropics. Is It Possible to Explain It Through Productive Variables?

Abstract: The objective of this work was to evaluate the longevity and its relationship with productive variables of Nelore cows in grazing systems of the Bolivian tropics. Retrospective data were used corresponding to 259 Nelore breed cows, primiparous and multiparous discarded with a total of 800 births, in the period between 2005 and 2019, belonging to the Cooperativa Agropecuaria Integral San Juan de Yapacaní (CAISY) located in the San Juan Japanese Communities, Santa Cruz, Bolivia. The variables analyzed were: Live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The values found in the age at first calving were similar to those reported by Flores & Ortiz (2010), the live weights of the cows to those reported by Segura-Correa, Magá n-Morforte & Centruion-Castro (2013), the calf weights at birth and at weaning above those shown by Santana et al (2012); Boligon, Brignardi Mercadante Lobo & Albunquerque. (2013); Chud et al (2014); Ikeda et al (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values found in the age at first calving were similar to those reported by Flores & Ortiz (2010), the live weights of the cows to those reported by Segura-Correa, Magá n-Morforte & Centruion-Castro (2013), the calf weights at birth and at weaning above those shown by Santana et al (2012); Boligon, Brignardi Mercadante Lobo & Albunquerque. (2013); Chud et al (2014); Ikeda et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The use of aggregated or integrated indicators in the beef-breeding systems for meat would allow evaluating the behavior of both the genotypes or racial groups involved, as well as the impact of the management strategies (non -genetic) on the biological and economic efficiency of the systems involved. Ikeda, Barbona, Hayashi, Pereira & Marini (2019) raised the need to use indicators of this nature that help to avoid the overvaluation of a character to the detriment of all those involved, allowing to identify the biotypes most adapted to the different environments existing in the place of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to use aggregated or integrated indicators in the cow-breeding systems for meat, because it would allow the evaluation of the behavior of both the genotypes and racial groups involved as well as the impact of the management strategies (non-genetic) on the both biological and economic [21] here using indicators of this nature would help to avoid the overvaluation of one of the characters involved in the characterization of a suitable cow for meat and would allow identifying the biotypes most adapted to the different environments existing in the place of evaluation. This is demonstrated with Figs.…”
Section: Number Of Calvingsmentioning
confidence: 99%
“…In addition, the production of beef cattle is influenced, among other factors, by the genotype of the animal associated with the environmental conditions to which it is subjected (Holgado and Rabasa, 1999). A previous work by (Ikeda et al, 2019), showed results on the relationship between the longevity of the productive variables, in this case the parturitionparturition interval is introduced as a reproductive variable and a greater number of years of information to be able to continue deepening the understanding of why some cows live longer than others.…”
Section: Introductionmentioning
confidence: 99%